I have 2 problem to solve with the Gauss metohd an im a little lost in that. someone help ?

#1

x + 3y - 2z = -5

2x + -y - z - w = -1

3x - 2y +4w = 1

-x + y - 3z - w = -6

#2

5x + y - z =1

2x - y - z = 0

thanks

Printable View

- May 25th 2006, 07:14 PMgotchyGauss method problem
I have 2 problem to solve with the Gauss metohd an im a little lost in that. someone help ?

#1

x + 3y - 2z = -5

2x + -y - z - w = -1

3x - 2y +4w = 1

-x + y - 3z - w = -6

#2

5x + y - z =1

2x - y - z = 0

thanks - May 26th 2006, 10:31 AMCaptainBlack

Now subtract twice the first row from the second, and

subtarct three times the first row from the third, and

add the first row to the fourth:

replace row three by row3+row4-row2, and row 4 by 11(2row4+row2)+row3:

Now replace row 4 by 4row4-61row3:

Now you need to check the arithmetic as I'm not too careful about that.

Then solve starting from the last equation and for the

variables, using the values for the variables found at each step to

substitute into the next earlier equation to solve for the next variable.

RonL